Effect of rheology evolution of a sustainable chemical grout, sodium-silicate based, for low pressure grouting in sensitive areas: Urbanized or historical sites. (10th January 2020) - Zullo, R.; Verdolotti, L.; Liguori, B.; Lirer, S.; Salzano de Luna, M.; Malara, P.; Filippone, G.
Graphical abstract: Highlights: Nano-SiO2 was used for improving shear mechanical properties of superfine cement grouts. Shear strength parameters and rheological properties of different grouts were determined. The optimal SP amounts of 1.5% and 0.75% were recommended for different grouts. Superfine cement grout property optimization and grouting effectiveness were discussed. Abstract: The subsoil consolidation in the archaeological sites or in areas with historic existing buildings (e.g. Pompeii) needs the use of ground improvement techniques that must guarantee the safeguarding of such relevant areas and structures. One of the best approaches in such cases is low pressure grouting. An experimental multidisciplinary study was carried out with the aim to design and characterize a sustainable chemical grout sodium silicate-based catalysed by NaHCO3 . The evolution from sol -to- glassy phase of the grouts was carefully investigated, furthermore the effectiveness of the grout has been verified either by lab tests or by real-scale field trials. The experimental findings suggested that it is possible to properly control the viscosity and gel-time of the grout modulating the amount of catalyst without affecting the final consolidation performances. Furthermore, the results at real-scale validate the safety of the above approach in cultural heritage applications, since it allowed a complete permeation of the soil without worsening its final properties.